2013
DOI: 10.1073/pnas.1312509110
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete cytokinesis and re-fusion of small mononucleated Hodgkin cells lead to giant multinucleated Reed–Sternberg cells

Abstract: Multinucleated Reed-Sternberg (RS) cells are pathognomonic for classical Hodgkin lymphoma (HL), and their presence is essential for diagnosis. How these giant tumor cells develop is controversial, however. It has been postulated that RS cells arise from mononucleated Hodgkin cells via endomitosis. Conversely, continuous single-cell tracking of HL cell lines by long-term time-lapse microscopy has identified cell fusion as the main route of RS cell formation. In contrast to growth-induced formation of giant Hodg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 50 publications
3
59
0
Order By: Relevance
“…In addition to these malignant cells, HL infiltrates comprise T cells, neutrophils, eosinophils, macrophages, fibroblast, plasma cells and mast cells. 1,2 The malignant cells are referred to as giant cells, also denominated Hodgkin Reed-Sternberg (HRS) cells, and their origin remains controversial. 1 Some theories point to either a fusion of B and non-B cells or mutation in germinal-center cells and loss of B cell receptor expression.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these malignant cells, HL infiltrates comprise T cells, neutrophils, eosinophils, macrophages, fibroblast, plasma cells and mast cells. 1,2 The malignant cells are referred to as giant cells, also denominated Hodgkin Reed-Sternberg (HRS) cells, and their origin remains controversial. 1 Some theories point to either a fusion of B and non-B cells or mutation in germinal-center cells and loss of B cell receptor expression.…”
Section: Overviewmentioning
confidence: 99%
“…1,2 The malignant cells are referred to as giant cells, also denominated Hodgkin Reed-Sternberg (HRS) cells, and their origin remains controversial. 1 Some theories point to either a fusion of B and non-B cells or mutation in germinal-center cells and loss of B cell receptor expression. 1,3,4 HRS cells seem to be dependent on both extracellular signals and endogenous signals derived from its own genome mutation.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunophenotype and the genetic features of HL and HRS cells are identical in these subtypes, but their clinical characteristics and association with EBV are different. How HRS cells develop is controversial and obscure; it has been postulated that these cells arise from mononucleated Hodgkin cells via endomitosis; however recently Rengstl et al by tracking the cells and their progeny for multiple generations demonstrated that the fusion of daughter cells, termed re-fusion, plays an essential role in the formation of HRS cells in HL cell lines 20. Importantly, cell fusion events occur almost exclusively between cells sharing the same ancestor and visualization of the microtubule network in time-lapse microscopy experiments revealed a persistent connection between daughter cells in the majority of re-fusion events 20.…”
Section: Classical Hodgkin Lymphomamentioning
confidence: 99%
“…Note the observed higher density of the IGF-1R in the present study in the mononuclear Hodgkin cells as compared with the multinuclear RS cells I and the IGF-1R, with stronger expression of the IGF-1R in the mononuclear Hodgkin than in the RS cells, should foster future studies. This is particularly pertinent because the enigmatic origin of the multinuclear RS cells has recently been illuminated by the findings that they arise by the re-fusion of daughter cells from small mononuclear Hodgkin cells that have undergone mitosis and constitute the proliferative compartment of the cHL tumour clone (Rengstl et al 2013).…”
Section: Fig 5 Igf-i In Cd68+mentioning
confidence: 99%